Integration of OPC UA Information Models into Enterprise Knowledge Graphs - Arno Weiss; Steffen Ihlenfeldt (Journal of Machine Engineering)
Building repositories of data relevant for enterprise operations requires harmonization of formats and semantics. OPC UA’s nodes-and-references data model shares basic elements with well-established semantic modeling technologies like RDF. This paper suggests the use of transformed OPC UA information models on the higher level of Enterprise Knowledge Graphs. It proposes good practice to integrate the separate domains by representing OPC UA servers as RDF-graphs and subsequently attaching them to Digital Twins embedded in Enterprise Knowledge Graph structures. The developed practice is implemented, applied to combine a server’s structure with an existing knowledge graph containing an Asset Administration Shell and released open source.